The Impact of Divorce in Islamic Law Children's Rights and Parental Obligations Post-Divorce - Dedisyah Putra; Muhadi Khalidi; Nuriza Acela (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2025)
Divorce is a significant and complex social phenomenon in modern society, which not only impacts the individuals involved but also affects the family as a whole, especially children. This research will discuss the impact of divorce in Islamic law, especially the obligations of parents towards children after divorce. This research is descriptive analytical in nature, exploring how the child's position is related to the child's rights and the obligations of parents after divorce. The research results show that in the context of Islamic law, divorce is not only seen from a legal perspective, but is also interpreted based on parental principles and ethics. This issue is becoming increasingly important in the current era, where the divorce rate is increasing, raising questions about children's rights and parental responsibilities.